Analysis Of The Influence Of Financial Ratio To Profitability Of Sharia Commercial Bank - Alsepta, Alvi; Hikmah, Khoirul; Satmoko, Agung; Sudaryatie, Sudaryatie; Kusumawati, Diana Anggraini (Journal of Business Innovation and Research, 2023)
This research aims to find out and analyze the influence of Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), and Operating Expense of Operating Income (OEOI) on Profitability in Sharia Commercial Banks in Indonesian in the period 2011-2020. This type of research is explanatory research and uses a quantitative approach. The population and sample of this study is the Indonesian Sharia Commercial Bank registered with the Financial Services Authority for the period 2011-2020, as many as 14 companies with saturated sampling techniques. The study used multiple regression analysis methods, classical assumption tests, and F and t hypothesis tests. The results of hypothesis testing showed that the four variables significantly influenced the profitability of Sharia commercial banks. Partially, the results of the hypothesis test showed that the variables Financing to Deposit Ratio and Non-Performing Financing had a negative and insignificant Influence on the Profitability of  Sharia Commercial Banks, the Capital Adequacy Ratio had a positive and insignificant Influence on the Probability of  Sharia Commercial Banks, and Operating Expenses of Operating Income negatively and significantly on the Profitability of  Sharia Commercial Banks. This study supports the results of Wahyudi & Kartikasari (2021), Ningsih & Dewi (2020), Aprilia & Soebroto (2020), and Yusuf (2017) and this study does not support the results of Devi (2021), Dewi (2020), and Marginingsih (2018).